The Role of Law in Realizing National Health Security - Lany Setyawati Kurniawan (Jurnal Health Sains, 2024)
National health security is a condition that enables the Indonesian nation to face and overcome various health threats, both originating from within the country and abroad. This research aims to analyze the role of law in realizing national health security. This research uses normative research methods. Data was collected through literature studies of legal regulations, books, journals and scientific articles related to law and health. The data analysis technique used is qualitative analysis. The research results show that law has an important role in realizing national health security, including its role in creating a just and equitable health system, protecting people's health rights, improving the quality of health services, ensuring the availability of safe and affordable medicines and health equipment, encouraging health research and development.